2014
DOI: 10.5194/tcd-8-2957-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glacier-like forms on Mars

Abstract: Abstract. Over 1300 glacier-like forms (GLFs) are located in Mars' mid-latitudes. These GLFs are visually similar to terrestrial valley glaciers, being predominantly composed of ice-dust mixtures and showing signs of downhill viscous deformation and of an expanded former extent. However, several fundamental aspects of their behaviour are virtually unknown, including temporal and spatial variations in mass balance, ice motion, landscape erosion and deposition, and hydrology. Here, we investigate the physical gl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…The correlation with D max is not surprising because the likelihood of observing larger craters in a given area should increase with its surface age (as well as with the size of the area). Despite the steepness of some SGLFs, the rate of resurfacing caused by internal deformation within them should be low, because we expect SGLFs to be thin (much thinner than VFFs generally) and this implies limited ice‐flow velocity. For instance, a tentative glaciological model (Karlsson et al, ), with its optimised plastic yield stress of 22 kPa and typical observed surface slope angles (15–30°, Figures c and supporting information, S38–S39), yields a ball‐park estimate for the thickness of SGLFs of only 11–24 m, which is consistent with their often concave surfaces (Hubbard et al, ). Although this estimate does not include a calculation of ice‐flow velocity (e.g., using Glen's flow law, Cuffey & Paterson, ) because the ice composition/rheology and temperature history are both uncertain, it points towards very subdued ice flow and limited reworking of their impact craters. If the SGLFs were much older than their apparent model ages, then their crater distributions would have reached near‐equilibrium, reflecting a balance of cratering and resurfacing rates.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The correlation with D max is not surprising because the likelihood of observing larger craters in a given area should increase with its surface age (as well as with the size of the area). Despite the steepness of some SGLFs, the rate of resurfacing caused by internal deformation within them should be low, because we expect SGLFs to be thin (much thinner than VFFs generally) and this implies limited ice‐flow velocity. For instance, a tentative glaciological model (Karlsson et al, ), with its optimised plastic yield stress of 22 kPa and typical observed surface slope angles (15–30°, Figures c and supporting information, S38–S39), yields a ball‐park estimate for the thickness of SGLFs of only 11–24 m, which is consistent with their often concave surfaces (Hubbard et al, ). Although this estimate does not include a calculation of ice‐flow velocity (e.g., using Glen's flow law, Cuffey & Paterson, ) because the ice composition/rheology and temperature history are both uncertain, it points towards very subdued ice flow and limited reworking of their impact craters. If the SGLFs were much older than their apparent model ages, then their crater distributions would have reached near‐equilibrium, reflecting a balance of cratering and resurfacing rates.…”
Section: Resultssupporting
confidence: 54%
“…The surface appearance of VFFs reflects the internal deformation and downslope transport of ice‐rich material (Hubbard et al, ). Flow‐parallel lineations observed on VFFs are deflected by topographic obstacles and can be traced over hundreds of kilometres (Dickson et al, ; Levy et al, ; Morgan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, such a retreat leaves glacial lineations or recessional moraines (Dowdeswell et al, ), which are not observed within Reuyl (Figure ). (3) No glacier‐related landforms, such as viscous flow features, lobate debris aprons with moats (Hauber et al, ), lineated valley fills, valley‐parallel lineations (Kress et al, ), drumlins, moraines (Burr et al, ), or other glacier‐like forms (Hubbard et al, ) are observed within Reuyl. Such a lack of typical glacial landforms leads us to eliminate an esker origin for SR within Reuyl (Burr et al, ; DiBiase et al, ; Lefort et al, ).…”
Section: Description and Analysismentioning
confidence: 99%
“…Of special interest are landforms that have long been interpreted as results of the presence and action of water and/or ice (e.g., Kargel et al, ), a notion that was supported when high‐resolution images became available and provided evidence for the aggradation and degradation of materials in a permafrost context (e.g., Morgenstern et al, ; Séjourné et al, ). Moreover, the lowlands cover the northern part of the bihemispheric latitude belt of ~30° to ~60°, which hosts a variety of possible periglacial and glacial landforms such as thermal contraction cracks, gullies, and viscous flow features, VFF (e.g., Harrison et al, ; Hubbard et al, ; Levy et al, ; Milliken et al, ). These and other landforms such as a layered latitude‐dependent mantle (LDM; Kostama et al, ; Kreslavsky & Head, ; Mustard et al, ) may represent a morphological record of recent ice ages (Head et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The geographical distribution of water‐ and/or ice‐related landforms can provide important constraints on their formation mechanism and the past Martian climate and its evolution. While the populations of some of the landforms that are relevant for the recent volatile and climate history of Mars have been localized (e.g., Balme et al, ; Dickson et al, ; Harrison et al, ; Hubbard et al, ; Kadish et al, ; Levy et al, ), a comprehensive mapping of all of them over the entire lowlands is still missing. However, given the small scale of many such landforms and surface textures, their large number and overlapping relationship over the vast expanse of the northern lowlands, it appears inefficient to map them individually and represent the results in a traditional map.…”
Section: Introductionmentioning
confidence: 99%